Including the spiritual dimension in the treatment of patients with affective disorders: validation of the spiritual distress and resources questionnaire (SDRQ) - Gerhard Stutz; Florian Hotzy; Andrea Eisenhut; Franziska von Keyserlingk; Hanspeter Moergeli; Simon Peng-Keller; Michael Rufer (BMC Psychology)
Abstract Background There is a lack of valid instruments for assessing spiritual resources and distress in the context of psychiatry and psychotherapy. To fill this gap, the newly developed Spiritual Distress and Resources Questionnaire (SDRQ) was studied in patients with affective disorders. The purpose of this study was to examine the psychometric properties of the SDRQ. Methods The SDRQ was administered to 177 patients with affective disorders. Measurement properties including reliability, structural validity and construct validity were analysed. In addition, a sub-sample of 41 participants completed the SDRQ a second time to assess test-retest reliability. Results Exploratory factor analysis confirmed that the 22 items of the SDRQ could be grouped into four subscales: spiritual distress, spiritual coping, immanence and transcendence. The spiritual distress, transcendence, immanence and spiritual coping subscales showed high internal consistency as indicated by Cronbach’s alpha coefficients (0.83–0.88). The construct validity of the SDRQ was supported by meaningful and significant correlations with established measures in the field. In particular, higher levels of spiritual distress were strongly associated with higher scores on the Hospital Anxiety and Depression Scale. Conclusion The results of this study suggest that the SDRQ is a reliable, valid and user-friendly screening tool for assessing spiritual distress, spiritual resources and spiritual coping in patients with affective disorders. The use of the SDRQ may be useful to adequately address and integrate spiritual aspects in a multimodal care approach.